Wakasikirei Satani? Christian subversion in sungura discourse - Mangeya, Hugh (Cogent OA, 2022)
The paper explores a unique type of theological discourse, discursively constructed through Zimbabwe’s sungura music that cannot be properly accounted for by existing theoretically definitions of gospel music. It is argued that this brand of religious discourse is a protest one which owes its character to the influence of Traditional African Religions (ATRs) that are practised in the country. The result of this dialogue between aspects of Christian theology and ATR is a brand of music that is perceived to be subverting the conventional understanding of gospel music. The paper argues that elements of subversion in Sungura discourse evolve around questions of divine benevolence, earthly rewards, justice and individuality as they manifest in Christianity. There is an eagerness, among critics, to focus on conventional gospel music while paying less heed to musical discourses which speak to Christianity in dialogic ways characterised by seeming contradictions. This paper addresses this hiatus. Critical Discourse Analysis (CDA) is used to explore the link between language and the practice of power through language. Analysis of songs is made within the naturalisation-neutralisation distinction framework in which discourse is employed with a view of either accepting or refuting/protesting against the existing relations of power. Thus, CDA is employed to explore how the subject positions themselves in relation to God.